Capgras Syndrome in the Young: Schizophrenia or Alzheimer Disease?. (January 2020) - Ng, Kok Pin; Wong, Benjamin; Xie, Wanying; Kandiah, Nagaendran
Abstract : This is a case report of an atypical presentation of early onset Alzheimer disease (EOAD) in a young patient with Capgras syndrome and cognitive impairment. The concurrent onset of psychiatric and cognitive symptoms prompted a detailed evaluation for a neurodegenerative disease. A 50-year-old male lawyer presented with low mood, apathy, delusions, and auditory hallucinations over 18 months. He considered his wife as an imposter and would require her text message to confirm her identity. He became more forgetful and had to give up his law practice. His neuropsychological assessment was impaired in all domains. Genetic testing revealed homozygosity for APOE e4 alleles. His magnetic resonance imaging showed predominant parietal and medial temporal atrophy, [18F]Fluorodeoxyglucose positron emission tomography showed frontal, parietal and posterior temporal hypometabolism and [18F]Flutemetamol positron emission tomography was positive for amyloid deposition, leading to the diagnosis of EOAD. This case highlights EOAD as a differential diagnosis in young patients who present with Capgras syndrome.